Análise morfológica de pequi sem e com espinho (fruto de Caryocar brasiliense) e seus efeitos em Drosophila melanogaster - Mendes, Mariana Gonçalves (2019)
Pequizeiro (Caryocar brasiliense) is one of the most prominent species in the Brazilian Cerrado and has variability in its physical and chemical characteristics, however, there is little data in the literature for individuals without thorns. It is an extractive economic specie and it is widely used in the feeding and prospecting molecules with pharmacological effects. Secondary metabolites of C. brasiliense have several functions as antioxidants and blockers of the action of specific enzymes that cause inflammation. The aim of this study was to analyze the morphological characteristics of fruits with and without thorn in the endocarp and to evaluate the effects of the ethanolic extract of the fruits, in vivo, with Drosophila melanogaster. Initially the weight, height and width of the fruit were determined; pyrene weight, width and length; pulp thickness and almond width. For experiments about the potential of pharmacological exploration of pequi components, flies of D. melanogaster from GMR-GAL4> UAS-eiger lineage, which develops the reduced eye phenotype, were treated with ethanolic extract of pulp and peel of fruits without and with thorn in the endocarp at different concentrations. From the characteristics of the fruits it was possible to evaluate the genetic diversity of pequizeiros. Fruits without thorn presented higher measurements than fruits with thorn. The Tocher and UPGMA clustering methods separated the pequi tree samples into three groups, one of which produced fruits with the highest values of external and internal characteristics. Two plants, B26 and B28 showed characteristics that distinguish them for breeding program. Our results also showed the possibility of using these fruits for pharmaceutical industry. Flies of D. melanogaster species treated with ethanolic extracts of pequi pulp and peel without and with thorn promoted the eye recovery. These data were corroborated by the reduction of eiger (human TNF- ortholog) and wengen (human TNF- receptor ortholog) transcript expression in D. melanogaster, both related to cell death processes. We verified that the ethanolic extract of pequi without and with thorns has positive effects and may act in the pathway of cell death process. Validate the use of D. melanogaster as an alternative model organism for the cell death and inflammation processes study as well as for better comprehension about natural compounds with pharmacological potential.